Infant temperament prospectively predicts general psychopathology in childhood. (12th August 2022) - Morales, Santiago; Tang, Alva; Bowers, Maureen E.; Miller, Natalie V.; Buzzell, George A.; Smith, Elizabeth; Seddio, Kaylee; Henderson, Heather A.; Fox, Nathan A.
Abstract: Recent models of psychopathology suggest the presence of a general factor capturing the shared variance among all symptoms along with specific psychopathology factors (e.g., internalizing and externalizing). However, few studies have examined predictors that may serve as transdiagnostic risk factors for general psychopathology from early development. In the current study we examine, for the first time, whether observed and parent-reported infant temperament dimensions prospectively predict general psychopathology as well as specific psychopathology dimensions (e.g., internalizing and externalizing) across childhood. In a longitudinal cohort ( N = 291), temperament dimensions were assessed at 4 months of age. Psychopathology symptoms were assessed at 7, 9, and 12 years of age. A bifactor model was used to estimate general, internalizing, and externalizing psychopathology factors. Across behavioral observations and parent-reports, higher motor activity in infancy significantly predicted greater general psychopathology in mid to late childhood. Moreover, low positive affect was predictive of the internalizing-specific factor. Other temperament dimensions were not related with any of the psychopathology factors after accounting for the general psychopathology factor. The results of this study suggest that infant motor activity may act as an early indicator of transdiagnostic risk. Our findings inform the etiology of general psychopathology and have implications for the early identification for children at risk for psychopathology.